Block copolymer binder as well as preparation method and application thereof
The block copolymer binder is prepared by template polymerization, so that it can be used in lithium-ion batteries, which solves the problem of reducing the flexibility of the electrode sheet caused by changes in the volume of silicon particles, achieves better adhesion and flexibility, and extends the battery life.
Patent Information
- Application Number
- CN202411579265.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-14
AI Technical Summary
In existing lithium-ion batteries, the volume of silicon particles changes greatly during charging and discharging, and the commonly used binder system is difficult to apply, resulting in reduced flexibility of the electrode sheet and brittleness, affecting subsequent processes.
The block copolymer binder is prepared by template polymerization, so that the silicone-philic segments and the flexible segments are distributed in an orderly manner on the molecular chain, thereby improving the adhesion and flexibility of the binder.
The adhesion between silicon particles and the flexibility of the electrode sheet are improved, the integrity and stability of the electrode sheet during the charge and discharge cycle are maintained, and the battery life is extended.
Smart Images

Figure CN119614113A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a block copolymer binder and a preparation method and application thereof. Background Art
[0002] In order to improve the energy density of the battery, the current development direction of lithium-ion batteries is to introduce silicon materials into the negative electrode so that its gram capacity can reach 4200mAh / g, while graphite is only about 320mAh / g. However, the volume of silicon particles themselves changes greatly during the charging and discharging process, and the currently commonly used carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) binder systems are difficult to apply. Therefore, a variety of acrylic acid series binders have been developed on the market for silicon-containing negative electrodes. The acrylic acid molecule itself contains carboxyl groups, which can form hydrogen bonds with some oxygen-containing functional groups on the surface of silicon particles, so that its adhesion will not be weakened in the electrolyte, and it can maintain the integrity of the electrode structure during the charging and discharging process. However, the polyacrylic acid binder will reduce the flexibility of the pole piece, which is manifested as the pole piece becoming brittle, which is not conducive to subsequent lamination processes.
[0003] In order to solve the problem of flexibility, most manufacturers copolymerize some acrylates and other flexible monomer units with acrylic acid to reduce the carboxyl content in the binder and improve the flexibility of the pole piece. However, this improvement is limited because the use of random copolymerization to prepare copolymers makes the flexible monomer units and acrylic acid irregularly distributed on the molecular chain. On the one hand, the flexible monomer units cannot exert their flexibility, and on the other hand, the acrylic acid monomers are difficult to tightly combine with silicon particles. Summary of the invention
[0004] In view of the above problems of the prior art, the present application provides a block copolymer binder, which adopts a template polymerization method to distribute the flexible segments and the segments containing polar groups at intervals. The specific technical solution is as follows:
[0005] In one aspect, the present application provides a block copolymer binder having the following structure:
[0006]
[0007] Wherein, X is a repeating unit composed of a silaphilic monomer, wherein the silaphilic monomer is a monomer having a polar group and capable of connecting to the surface of silicon particles through a chemical bond; Y is a repeating unit composed of a flexible monomer; and a, b, and m are all integers greater than 1.
[0008] In a possible implementation, the silicophilic monomer includes at least one of a carboxyl-containing monomer, an amine-containing monomer, a sulfonic acid-containing monomer, an aldehyde-containing monomer, a phosphate-containing monomer, a phenolic hydroxyl-containing monomer, a sulfate-containing monomer, and a sulfonamide-containing monomer.
[0009] In a possible implementation manner, the silaphilic monomer satisfies at least one of the following characteristics:
[0010] The carboxyl-containing monomer includes at least one of acrylic acid, crotonic acid, and methacrylic acid;
[0011] The monomer containing an amino group includes at least one of methyl butylene acid, acrylamide, methacrylamide and diallylamine.
[0012] In a possible implementation manner, the flexible monomer includes at least one of methyl methacrylate, butyl methacrylate, octadecyl acrylate, and allyl polyoxyethylene ether.
[0013] On the other hand, the present application provides a method for preparing a block copolymer binder, the preparation method comprising:
[0014] S1: Provides silanophilic monomers, template polymers, and flexible monomers;
[0015] S2: adding the silophilic monomer, the template polymer and the flexible monomer to the first solvent in proportion under a protective atmosphere, adjusting the pH, and obtaining a mixed solution;
[0016] S3: adding an initiator to the mixed solution, heating and aging, and adjusting the pH to precipitate the template polymer to obtain a block copolymer solution;
[0017] S4: extracting the block copolymer in the block copolymer solution to obtain a block copolymer binder.
[0018] In a possible implementation, the template polymer can serve as a polymerization template for the silaphilic monomer, and the template polymer includes at least one of polyacrylamide, polymethacrylamide, polyallylamine, polyacrylic acid, and polymethacrylic acid.
[0019] In a possible implementation manner, the mixed solution satisfies at least one of the following characteristics:
[0020] The amount of the silaphilic monomer added is 4%-16% of the mass of the first solvent;
[0021] The amount of the flexible monomer added is 4%-16% of the mass of the first solvent;
[0022] The molar ratio of the silaphilic monomer to the template polymer is 1:1-1.5;
[0023] The pH of the mixed solution is 4-9.
[0024] In a possible embodiment, the initiator satisfies at least one of the following characteristics:
[0025] The initiator comprises at least one of sulfate, redox initiator system, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline, and azobiscyanovaleric acid;
[0026] The added amount of the initiator is 0.5%-1% of the total mass of the silophilic monomer and the flexible monomer.
[0027] In a possible implementation manner, step S3 satisfies at least one of the following characteristics:
[0028] The heating temperature is 40-80°C;
[0029] The heating time is 2-6h;
[0030] The aging time is 24-48h.
[0031] In a possible implementation manner, a second solvent is added to the block copolymer solution to extract the block copolymer binder, and the second solvent includes at least one of ethanol, propanol, butanol, and tetrahydrofuran.
[0032] Based on the above technical solution, this application has the following beneficial effects:
[0033] 1. The present application provides a block copolymer binder, comprising a silicon-philic segment composed of repeating units of a silicon-philic monomer, and a flexible segment composed of repeating units of a flexible monomer, and the flexible segment and the silicon-philic segment are orderly spaced and distributed on the molecular chain of the block copolymer binder, which is conducive to better exerting the advantages of each segment; the silicon-philic segment can interact with the surface of silicon particles, improve the adhesion of the binder to the silicon particles, and then improve the adhesion between silicon particles; the flexible segment is conducive to improving the flexibility and processability of the binder, thereby improving the flexibility of the electrode plate, and maintaining the integrity and stability of the electrode plate during the battery charge and discharge cycle.
[0034] 2. The present application also provides a method for preparing a block copolymer binder, which enables the flexible segments and silicon-philic segments on the molecular chain of the block copolymer binder to be spaced apart by template polymerization, thereby avoiding the reduction of the adhesiveness and flexibility of the binder due to the irregular arrangement of monomers. In this method, the template polymer can serve as a polymerization template for silicon-philic monomers, so that the silicon-philic monomers are orderly and concentratedly distributed on the polymer chain, which is conducive to exerting their adhesion properties to electrode materials; and the template polymer can be recycled and reused, which helps to reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions and advantages in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 : A schematic diagram of a block copolymer provided in an embodiment of the present application acting on silicon particles;
[0037] Figure 2 : A schematic diagram of the preparation of a block copolymer binder provided in an embodiment of the present application;
[0038] Figure numerals: 1-silicon particles, 2-silicophilic segments, 3-flexible segments, 4-template polymers, 5-silicophilic monomers, 6-flexible monomers. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0040] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values included in the numerical range and all subranges included in the numerical range.
[0041] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.
[0042] A block copolymer binder provided in an embodiment of the present application is described below. The block copolymer binder has the following structure:
[0043]
[0044] Among them, X is a repeating unit composed of a silicon-philic monomer, which is a monomer having a polar group and can be connected to the surface of silicon particles through a chemical bond; Y is a repeating unit composed of a flexible monomer; a, b, and m are all integers greater than 1. That is, on the molecular chain of the block copolymer binder, the repeating units of the silicon-philic monomer constitute the silicon-philic segment, and the repeating units of the flexible monomer constitute the flexible segment. The silicon-philic segment and the flexible segment are distributed at intervals, which is conducive to better exerting the advantages of each segment. Figure 1 It can be seen that the silicon-philic chain segments can interact with silicon particles, improve the adhesion of the block copolymer binder to the silicon particles, and then improve the adhesion between the silicon particles; the flexible chain segments are beneficial to improving the flexibility and processability of the binder, so that the binder can adapt to the volume expansion of silicon particles during the charging and discharging process, and produce electrode plates with good flexibility and stability.
[0045] In some embodiments, the silicon-philic monomer includes at least one of a carboxyl-containing monomer, an amine-containing monomer, a sulfonic acid-containing monomer, an aldehyde-containing monomer, a phosphate-containing monomer, a phenolic hydroxyl-containing monomer, a sulfate-containing monomer, and a sulfonamide-containing monomer. Oxygen-containing functional groups exist on the surface of silicon particles. Therefore, the introduction of polar group-containing monomers into the molecular chain of the copolymer enables the block copolymer to interact with the functional groups on the surface of the silicon particles, which is beneficial to improving the adhesion of the block copolymer binder to the silicon particles, thereby improving the adhesion between the silicon particles.
[0046] Specifically, the carboxyl group-containing monomer includes at least one of acrylic acid, crotonic acid, and methacrylic acid.
[0047] Specifically, the monomer containing an amine group includes at least one of methyl butylene acid, acrylamide, methacrylamide, and diallylamine. The monomer containing a carboxyl group and an amine group can be ionized in water, which is conducive to combining with the corresponding template polymer and promoting the occurrence of a polymerization reaction; and can interact with oxygen-containing functional groups on the surface of silicon particles, thereby enhancing the adhesion strength of the block copolymer binder to the silicon particles, thereby improving the flexibility and stability of the electrode plate.
[0048] In some embodiments, the flexible monomer includes at least one of methyl methacrylate, butyl methacrylate, octadecyl acrylate, and allyl polyoxyethylene ether. The flexible segment includes a repeating unit composed of a flexible monomer. The introduction of the flexible segment into the block copolymer binder helps to improve the overall flexibility and processability of the block copolymer binder, can be used to buffer the volume expansion of the electrode material, and can produce a battery pole piece with better flexibility and stability.
[0049] refer to Figure 2The template polymerization principle shown in the figure, the embodiment of the present application also provides a method for preparing a block copolymer binder, the block copolymer binder is prepared by the template polymerization method, so that the flexible segment and the silicon-philic segment are spaced and distributed on the molecular chain of the block copolymer binder, which is conducive to giving full play to the advantages of each segment. Specifically comprising the following steps:
[0050] S1: Provides silanophilic monomers, template polymers, and flexible monomers;
[0051] In some embodiments, the template polymer includes at least one of polyacrylamide, polymethacrylamide, polyallylamine, polyacrylic acid, and polymethacrylic acid. The template polymer can serve as a polymerization template for the silicon-philic monomer, and the template polymer can interact with the monomer through hydrogen bonding, van der Waals force, covalent bonding, or electrostatic attraction, etc. The template polymerization can make the silicon-philic monomer present a concentrated distribution of blocks in the polymer chain, which is conducive to the adhesion of the silicon-philic chain segment; and the template polymer can be recycled and reused, which helps to reduce production costs.
[0052] Preferably, the template polymer and the silicophilic monomer are connected by hydrogen bonds, which, as an intermolecular force, can bind the monomer to the template polymer and make it easy to remove the template polymer after the polymerization reaction. Exemplarily, when the silicophilic monomer is selected from monomers containing carboxyl groups, the corresponding template polymer is selected from polymers containing amine groups, including at least one of polyacrylic acid and polymethacrylic acid. Exemplarily, when the silicophilic monomer is selected from monomers containing amine groups, the corresponding template polymer is selected from polymers containing carboxyl groups.
[0053] S2: adding the silicophilic monomer, the template polymer and the flexible monomer to the first solvent in proportion under a protective atmosphere, adjusting the pH, and obtaining a mixed solution;
[0054] Specifically, the first solvent can dissolve the silicon-philic monomer, the flexible monomer, the block polymer binder and the template polymer. Preferably, the first solvent is water, which can completely dissolve the monomer and the polymer and facilitate pH adjustment by adding inorganic acid or inorganic base in subsequent steps.
[0055] Specifically, the protective gas includes nitrogen, helium, argon, neon, krypton, etc., which prevents the raw materials from contacting with air during the mixing process and avoids the raw materials from generating oxide impurities.
[0056] In some embodiments, the amount of the silaphilic monomer added is 4%-16% of the mass of the first solvent; it is understandable that the amount of the silaphilic monomer added can be any point value between 4%-16% of the mass of the first solvent; illustratively, the amount of the silaphilic monomer added is 4%, 5%, 7.5%, 10%, 16% and the like of the mass of the first solvent. Preferably, the amount of the silaphilic monomer added is 9%-11% of the mass of the first solvent. Within the above range, the silaphilic monomer can be fully dissolved in the first solvent and uniformly dispersed in the first solvent, which is conducive to full contact with the template polymer during the polymerization reaction, thereby improving the reaction rate and conversion rate.
[0057] Specifically, the amount of the flexible monomer added is 4%-16% of the mass of the first solvent; it can be understood that the amount of the flexible monomer added can be any point value between 4%-16% of the mass of the first solvent; illustratively, the amount of the flexible monomer added is 4%, 5%, 7.5%, 10%, 16% and the like of the mass of the first solvent. Preferably, the amount of the flexible monomer added is 9%-11% of the mass of the first solvent. In this way, the flexible monomer can be fully dissolved in the first solvent and evenly mixed with the silicon-philic monomer, which is conducive to the polymerization reaction.
[0058] Preferably, the mass ratio of the silicon-philic monomer to the flexible monomer is 1:1.
[0059] Specifically, the molar ratio of the silaphilic monomer to the template polymer is 1:1-1.5; it can be understood that the molar ratio of the silaphilic monomer to the template polymer can be any point value in the range of 1:1-1.5; illustratively, the molar ratio of the silaphilic monomer to the template polymer is 1:1, 1:1.1, 1:1.2, 1:1.4, 1:1.5, etc. In this way, the molar ratio of the silaphilic monomer to the template polymer is controlled within the above range, so that during the polymerization reaction, all the silaphilic monomers can be connected to the polymer template site and polymerized along the template chain, which helps the monomers to react completely and improve the yield.
[0060] In some embodiments, an inorganic acid or an inorganic base is added to adjust the pH of the mixed solution to 4-9. It is understandable that the pH of the mixed solution can be any value between 4-9, which is not enumerated here. In this way, adjusting the pH of the mixed solution to the above range can effectively prevent the template polymer from precipitating, so that the monomer and the template polymer in the solution are fully dissolved and mixed evenly. Preferably, the pH of the mixed solution is adjusted to 7.
[0061] Specifically, the inorganic base includes at least one of potassium hydroxide, sodium hydroxide, and sodium bicarbonate; the inorganic acid includes at least one of hydrochloric acid, sulfuric acid, carbonic acid, and phosphoric acid.
[0062] S3: adding an initiator to the mixed solution, heating and aging, and adjusting the pH to precipitate the template polymer to obtain a block copolymer solution;
[0063] In some embodiments, the initiator includes at least one of sulfate, redox initiator system, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline, and azobiscyanovaleric acid, which can promote the polymerization reaction of the silicon-philic monomer and the flexible monomer, and help accelerate the polymerization reaction rate.
[0064] Specifically, the amount of the initiator added is 0.5%-1% of the total mass of the silicophilic monomer and the flexible monomer; it can be understood that the amount of the initiator added can be any point value between 0.5%-1% of the total mass of the monomer; illustratively, the amount of the initiator added is 0.5%, 0.6%, 0.7%, 0.8%, 1% and the like of the total mass of the monomer. In this way, controlling the amount of the initiator added within the above range is conducive to the initiator fully contacting with the silicophilic monomer and the flexible monomer, so that the monomer reacts completely, thereby improving the yield. Preferably, the amount of the initiator added is 1% of the total mass of the silicophilic monomer and the flexible monomer.
[0065] In some embodiments, the heating temperature is set to 40-80°C; it can be understood that the heating temperature can be any point value in the range of 40-80°C; for example, the heating temperature is 40°C, 60°C, 65°C, 70°C, 80°C, etc. In this way, controlling the heating temperature within the above range is conducive to causing the copolymerization reaction to occur, so that the monomer reaches the temperature required for polymerization; and it is conducive to increasing the reaction rate and promoting the complete reaction of the monomer.
[0066] Specifically, the heating time is set to 2-6 hours; it can be understood that the heating time can be any point value in 2-6 hours; exemplary, the heating time is 2 hours, 2.5 hours, 3 hours, 4 hours, 6 hours, etc. Controlling the heating time within the above range is conducive to the full progress of the polymerization reaction.
[0067] Specifically, aging is performed after stopping heating, and the aging time is 24-48 hours; it can be understood that the aging time can be any point value between 24-48 hours; illustratively, the aging time is 24 hours, 28 hours, 30 hours, 40 hours, 48 hours, etc. Aging is helpful for the subsequent purification process, can effectively avoid the precipitation loss of block polymers during purification, and is conducive to improving the yield.
[0068] In some embodiments, the template polymer is precipitated by adjusting the pH. Specifically, when the template polymer is at least one of polyacrylamide, polymethacrylamide, and polyallylamine, the template polymer can be precipitated by adding an inorganic base to adjust the pH of the mixed solution to 12-14. It is understandable that the pH of the mixed solution can be any point value between 12-14, which is not enumerated here. Specifically, the inorganic base includes at least one of potassium hydroxide, sodium hydroxide, and sodium bicarbonate.
[0069] Specifically, when the template polymer is at least one of polyacrylic acid and polymethacrylic acid, adding an inorganic acid to adjust the pH of the mixed solution to 0-2 can cause the template polymer to precipitate. It is understandable that the pH of the mixed solution can be any point value between 0-2, which is not enumerated here. Specifically, the inorganic acid includes at least one of hydrochloric acid, sulfuric acid, carbonic acid, and phosphoric acid.
[0070] S4: extracting the block copolymer in the block copolymer solution to obtain a block copolymer binder.
[0071] In some embodiments, the block copolymer is extracted by adding a second solvent to the block copolymer solution, the second solvent is a poor solvent for the block copolymer binder, and the second solvent includes at least one of ethanol, propanol, butanol, and tetrahydrofuran. Wherein, the solubility of the block copolymer binder in the first solvent is greater than its solubility in the second solvent, and the block copolymer binder is extracted from the reaction system by utilizing the difference in solubility of the block copolymer binder in different solvents, and it is beneficial to remove impurities in the product.
[0072] In some other embodiments, the solvent in the block copolymer solution is evaporated by an evaporation method to separate the block copolymer binder.
[0073] In some embodiments, step S4 further comprises a purification step, dissolving the extracted block copolymer in a first solvent, then adding a second solvent to extract the block polymer binder, repeating the above steps at least once to obtain a purified block copolymer binder. Preferably, the first solvent is water and the second solvent is ethanol.
[0074] On the other hand, the present application also provides an electrode plate, comprising the block copolymer binder as described above, or comprising a block copolymer binder prepared by the method for preparing the block copolymer binder as described above.
[0075] In some embodiments, the block copolymer binder is applied to negative electrode sheets with high silicon content, wherein the silicon content of the negative electrode sheets is greater than or equal to 20%. The block copolymer binder can effectively improve the adhesion between silicon particles and improve the flexibility of the negative electrode sheets, thereby ensuring the integrity of the negative electrode sheets during the charge and discharge process, and is beneficial to improving the cycle stability performance of the battery.
[0076] The specific embodiments of the present application are introduced below in conjunction with the above-mentioned block copolymer binder. The following examples describe the technical scheme of the present application in more detail, and these examples are only used for illustrative purposes, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the disclosure of the present application. The reagents used in the examples can be obtained by commercial purchase or synthesized according to conventional methods, and can be used directly without further processing, and the instruments and devices used in the examples can be obtained by commercial purchase.
[0077] Example 1
[0078] This embodiment provides a block copolymer binder, which is prepared by the following steps:
[0079] 1. Dissolve 0.5 parts of acrylic acid monomer, 0.6 parts of polyallylamine, and 0.5 parts of methyl methacrylate monomer in 5 parts of solvent water, introduce nitrogen for 30 minutes, adjust the pH to 7, and obtain a mixed solution;
[0080] 2. Add 0.005 parts of potassium persulfate to the mixed solution and heat it at 60°C for 4 hours. After stopping the heating, age it for 24 hours, and then adjust the pH to 14 with sodium hydroxide to precipitate the template polymer to obtain a block copolymer solution.
[0081] 3. Add ethanol to the block copolymer solution to precipitate the block copolymer, dissolve the block copolymer with water, and then precipitate the product with ethanol, repeat the above dissolution-precipitation steps three times to obtain a polyacrylic acid-methyl methacrylate block copolymer binder.
[0082] Furthermore, the above-obtained polyacrylic acid-methyl methacrylate block copolymer binder is used to prepare a negative electrode plate, and the specific steps are as follows:
[0083] 1. Take an appropriate amount of polyacrylic acid-polymethyl methacrylate block copolymer binder and add it to water, stir it magnetically for 12 hours to obtain a binder glue solution;
[0084] 2. Add silicon, graphite, and carbon nanotubes (CNT) to water in order, and then add a binder glue solution, wherein the ratio of silicon, graphite, CNT, and binder is 10:80:10:2, and adjust the solid content to 40%-60% to obtain a mixed slurry;
[0085] 3. The mixed slurry is centrifugally dispersed, the disperser speed is set to 2000 rpm, and the dispersion time is 10 min to obtain the negative electrode slurry;
[0086] 4. Use a transfer coater to coat the slurry, use carbon-coated copper foil as the substrate, and dry at 100°C. After the solution is dried, the negative electrode sheet is obtained.
[0087] Example 2
[0088] This embodiment provides a block copolymer adhesive, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that 0.5 parts of acrylic acid monomer, 0.6 parts of polyallylamine, and 0.5 parts of butyl acrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-butyl acrylate block copolymer adhesive is prepared.
[0089] Furthermore, the above-obtained polyacrylic acid-butyl acrylate block copolymer binder is used to prepare the negative electrode sheet, and the specific steps and parameters used are consistent with those in the above-mentioned embodiment 1, which will not be described in detail.
[0090] Example 3
[0091] This embodiment provides a block copolymer binder, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that 0.2 parts of acrylic acid monomer, 0.24 parts of polyallylamine, and 0.8 parts of butyl methacrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-butyl methacrylate block copolymer binder is prepared.
[0092] Furthermore, the above-obtained polyacrylic acid-butyl methacrylate block copolymer binder is used to prepare the negative electrode sheet, and the specific steps and parameters used are consistent with those in the above-mentioned embodiment 1, which will not be described in detail.
[0093] Example 4
[0094] This embodiment provides a block copolymer binder, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that 0.4 parts of acrylic acid monomer, 0.48 parts of polyallylamine, and 0.6 parts of butyl methacrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-butyl methacrylate block copolymer binder is prepared.
[0095] Furthermore, the above-obtained polyacrylic acid-butyl methacrylate block copolymer binder is used to prepare the negative electrode sheet, and the specific steps and parameters used are consistent with those in the above-mentioned embodiment 1, which will not be described in detail.
[0096] Example 5
[0097] This embodiment uses the polyacrylic acid-polymethyl methacrylate block copolymer binder prepared in Example 1 to prepare the negative electrode plate. The similarities with Example 1 are not repeated here. The difference from Example 1 is that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0098] Example 6
[0099] This embodiment uses the polyacrylic acid-polybutyl acrylate block copolymer binder prepared in Example 2 to prepare the negative electrode plate. The similarities with Example 2 are not repeated here. The difference from Example 2 is that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0100] Example 7
[0101] This embodiment uses the polyacrylic acid-butyl methacrylate block copolymer binder prepared in Example 3 to prepare the negative electrode plate. The similarities with Example 3 are not repeated here. The difference from Example 3 is that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0102] Example 8
[0103] This embodiment uses the polyacrylic acid-butyl methacrylate block copolymer binder prepared in Example 4 to prepare the negative electrode plate. The similarities with Example 4 are not repeated here. The difference from Example 4 is that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0104] Example 9
[0105] The present embodiment provides a block copolymer binder, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that 0.1 parts of acrylic acid monomer, 0.4 parts of methyl butylene acid monomer, 0.6 parts of polyallylamine, and 0.5 parts of octadecyl acrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-methyl butylene acid-octadecyl acrylate block copolymer binder is prepared.
[0106] Furthermore, the above-obtained polyacrylic acid-methylbutenoic acid-octadecyl acrylate block copolymer binder is used to prepare a negative electrode plate, which is different from Example 1 in that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0107] Example 10
[0108] The present embodiment provides a block copolymer binder, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that: 0.5 parts of acrylic acid monomer, 0.6 parts of polyacrylic acid, 0.2 parts of butyl methacrylate monomer and 0.3 parts of allyl polyoxyethylene ether monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; after heating and aging, the pH is adjusted to 1 by hydrochloric acid; and finally a polyacrylamide-butyl methacrylate-allyl polyoxyethylene ether block copolymer binder is prepared.
[0109] Furthermore, the anode electrode sheet was prepared by using the polyacrylamide-butyl methacrylate-allyl polyoxyethylene ether block copolymer binder obtained above, which was different from Example 1 in that the ratio of silicon, graphite, CNT and binder in the cathode electrode sheet was 80:10:10:2.
[0110] Embodiment 11
[0111] The present embodiment provides a block copolymer binder, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that: 0.2 parts of acrylamide monomer, 0.3 parts of diallylamine, 0.6 parts of polyacrylic acid, 0.2 parts of butyl methacrylate monomer and 0.3 parts of octadecyl acrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; after heating and aging, the pH is adjusted to 1 by hydrochloric acid; and finally a polyacrylamide-diallylamine-butyl methacrylate-octadecyl acrylate block copolymer binder is prepared.
[0112] Furthermore, the above-obtained polyacrylamide-diallylamine-butyl methacrylate-octadecyl acrylate block copolymer binder is used to prepare the negative electrode plate, which is different from Example 1 in that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0113] Comparative Example 1
[0114] The negative electrode sheet is prepared by using a carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) binder system. The specific steps and parameters used are consistent with those in the aforementioned embodiment 1 and are not described in detail.
[0115] Comparative Example 2
[0116] Polyacrylic acid is used as a binder to prepare the negative electrode plate. The specific steps and parameters used are consistent with those in the above-mentioned embodiment 1 and are not described in detail.
[0117] Comparative Example 3
[0118] CMC+SBR is used as a binder to prepare the negative electrode sheet. The specific steps and parameters used are consistent with those in the aforementioned Example 5 and will not be described in detail.
[0119] Comparative Example 4
[0120] Polyacrylic acid is used as a binder to prepare the negative electrode plate. The specific steps and parameters used are consistent with those in the aforementioned Example 5 and will not be described in detail.
[0121] Comparative Example 5
[0122] This comparative example provides a copolymer binder, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that 0.5 parts of acrylic acid monomer and 0.5 parts of butyl methacrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-polybutyl methacrylate copolymer binder is prepared.
[0123] Furthermore, the above-obtained polyacrylic acid-polybutyl methacrylate copolymer binder is used to prepare the negative electrode sheet, and the specific steps and parameters used are consistent with those in the above-mentioned embodiment 1, which will not be described in detail.
[0124] Comparative Example 6
[0125] This comparative example provides a copolymer binder, and the similarities with Example 1 are not repeated here. The difference from Example 1 is that 0.2 parts of acrylic acid monomer and 0.8 parts of butyl methacrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-polybutyl methacrylate copolymer binder is prepared.
[0126] Furthermore, the above-obtained polyacrylic acid-polybutyl methacrylate copolymer binder is used to prepare the negative electrode sheet, and the specific steps and parameters used are consistent with those in the above-mentioned embodiment 1, which will not be described in detail.
[0127] Comparative Example 7
[0128] This comparative example uses the polyacrylic acid-butyl methacrylate copolymer binder prepared in comparative example 5 to prepare the negative electrode plate. The similarities with comparative example 5 are not repeated here. The difference from comparative example 5 is that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0129] Comparative Example 8
[0130] This comparative example uses the polyacrylic acid-butyl methacrylate copolymer binder prepared in comparative example 6 to prepare the negative electrode plate. The similarities with comparative example 6 are not repeated here. The difference from comparative example 6 is that the ratio of silicon, graphite, CNT and binder in the negative electrode plate is 80:10:10:2.
[0131] Comparative Example 9
[0132] This comparative example provides a copolymer binder, and the similarities with comparative example 5 are not repeated here. The difference between this comparative example and comparative example 5 is that: 0.4 parts of acrylic acid monomer and 0.6 parts of butyl methacrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-polybutyl methacrylate copolymer binder is prepared.
[0133] Furthermore, the above-obtained polyacrylic acid-polybutyl methacrylate copolymer binder is used to prepare a negative electrode sheet. The similarities with Comparative Example 5 are not repeated here. The difference from Comparative Example 5 is that the ratio of silicon, graphite, CNT and binder in the negative electrode sheet is 80:10:10:2.
[0134] Comparative Example 10
[0135] This comparative example provides a copolymer binder, and the similarities with comparative example 5 are not repeated here. The difference between it and example 5 is that: 0.6 parts of acrylic acid monomer and 0.4 parts of butyl methacrylate monomer are dissolved in 5 parts of solvent water, nitrogen is introduced for 30 minutes, and the pH is adjusted to 7 to obtain a mixed solution; finally, a polyacrylic acid-polybutyl methacrylate copolymer binder is prepared.
[0136] Furthermore, the above-obtained polyacrylic acid-polybutyl methacrylate copolymer binder is used to prepare a negative electrode sheet. The similarities with Comparative Example 5 are not repeated here. The difference from Comparative Example 5 is that the ratio of silicon, graphite, CNT and binder in the negative electrode sheet is 80:10:10:2.
[0137] The flexibility test of the negative electrode plates prepared in the above embodiments and comparative examples was carried out, and the test method used was as follows: According to GB / T 1731-2020, the flexibility of the electrode plates was measured using a paint film flexibility tester, and the flexibility of the electrode plates was represented by the minimum shaft rod diameter without breaking the electrode plates. The smaller the diameter, the better the flexibility of the electrode plates. The test results are shown in Table 1:
[0138] Table 1
[0139]
[0140] The negative electrode sheets prepared in the above-mentioned embodiments and comparative examples were cut and assembled into batteries, and the capacity retention rate after 1000 cycles was measured. The test results are shown in Table 2:
[0141] Table 2
[0142]
[0143]
[0144] Referring to the test results in Tables 1 and 2, combined with Examples 1-4, it can be seen that by selecting different flexible monomers and changing the ratio of the silicon-philic monomer to the flexible monomer to prepare the block copolymer binder, the minimum unbroken shaft rod diameter of the negative electrode pole piece containing the above block copolymer binder is 1 mm, and the capacity retention rate of the battery containing the above negative electrode pole piece after 1000 cycles is greater than or equal to 80%, which proves that the negative electrode pole piece provided in the embodiment of the present application exhibits good flexibility and stability, which is beneficial to improving the cycle stability of the battery and extending the battery life.
[0145] In combination with Examples 1-8, it can be seen that in Examples 5-8, the block copolymer binder prepared in Examples 1-4 is applied to the negative electrode sheet with a silicon content of 80%. Since the volume of silicon particles changes greatly during the charge and discharge process, affecting the structural integrity of the sheet, the flexibility of the high silicon content negative electrode sheet in Examples 5-8 is reduced compared to the flexibility of the negative electrode sheet in Examples 1-4, but still maintains a high flexibility level, and can effectively maintain the integrity and stability of the negative electrode sheet structure.
[0146] Combining Examples 1-11 and Comparative Examples 1-4, it can be seen that Comparative Examples 1-4 use CMC+SBR binder system or pure polyacrylic acid binder to prepare negative electrode plates, and the negative electrode plates show poor flexibility, and the capacity retention rate of the battery applied is less than 68%; when the block copolymer binder prepared in Examples 1-11 is applied to the negative electrode plates, the negative electrode plates can show good flexibility, and the capacity retention rate of the battery applied is higher than 78%, which proves that the block copolymer binder in the examples of the present application can better maintain the integrity of the plates, so that the capacity retention rate of the battery reaches an extremely high level.
[0147] In combination with Examples 1-11 and Comparative Examples 5-10, it can be seen that in Comparative Examples 5-10, the polymer binder is prepared by a random copolymerization method, and the minimum unbroken shaft rod diameter of the negative electrode pole piece containing the polymer binder is greater than or equal to 4 mm, while the minimum unbroken shaft rod diameter of the negative electrode pole piece prepared in Examples 1-11 is less than or equal to 1.5 mm; and the batteries prepared from the negative electrode pole pieces in Examples 1-11 show a capacity retention rate higher than 78%, which is significantly better than Comparative Examples 5-10, proving that the block copolymer binder of the present application has good flexibility and adhesion, and further proving that compared with irregularly distributed flexible monomers and silicon-philic monomers, the block-distributed flexible segments and silicon-philic segments in the present application can give full play to their flexibility and adhesion.
[0148] Combining Examples 5-11 and Comparative Examples 7-10, it can be seen that in Example 5-11, two or more silicon-philic monomers and flexible monomers are copolymerized to obtain a block copolymer binder, and applied to a negative electrode sheet with a silicon content of 80%. The minimum unbroken shaft rod diameter of the above-mentioned negative electrode sheet is less than or equal to 1.5 mm, and has good flexibility. When the polymer binder prepared by random copolymerization is applied to a negative electrode sheet with a high silicon content in Comparative Examples 7-10, the minimum unbroken shaft rod diameter of the negative electrode sheet is greater than or equal to 5 mm, showing poor flexibility. And when the negative electrode sheet in Examples 5-11 is applied to a battery, the capacity retention rate of the battery after 1000 cycles is higher than 78%, while the capacity retention rate of the negative electrode sheet in Comparative Examples 7-10 applied to the battery is lower than 53%, proving that the block copolymer binder prepared in the examples of the present application can effectively reduce the damage to the negative electrode sheet caused by the volume expansion of the silicon material, and enhance the stability of the sheet structure, and can be applied to negative electrode sheets with a high silicon content.
[0149] It should be noted that the various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0150] What is described above are only some embodiments of the present application and are not intended to limit the present application. Those skilled in the art should understand that the present application may undergo various changes and improvements, and any modifications, equivalent substitutions and improvements made in accordance with the present application shall fall within the scope of protection required by the present application.
Claims
1. A block copolymer binder, characterized in that: The block copolymer binder has the following structure: Wherein, X is a repeating unit composed of a silaphilic monomer, and the silaphilic monomer is a monomer containing a polar group; Y is a repeating unit composed of a flexible monomer; and a, b, and m are all integers greater than 1.
2. The block copolymer adhesive according to claim 1, characterized in that The silicophilic monomer includes at least one of a carboxyl-containing monomer, an amine-containing monomer, a sulfonic acid-containing monomer, an aldehyde-containing monomer, a phosphate-containing monomer, a phenolic hydroxyl-containing monomer, a sulfate-containing monomer, and a sulfonamide-containing monomer.
3. The block copolymer adhesive according to claim 1 or 2, characterized in that The silaphilic monomer satisfies at least one of the following characteristics: The carboxyl-containing monomer includes at least one of acrylic acid, crotonic acid, and methacrylic acid; The monomer containing an amino group includes at least one of methyl butylene acid, acrylamide, methacrylamide and diallylamine.
4. The block copolymer adhesive according to claim 1, characterized in that The flexible monomer includes at least one of methyl methacrylate, butyl methacrylate, octadecyl acrylate, and allyl polyoxyethylene ether.
5. The method for preparing the block copolymer binder according to any one of claims 1 to 4, characterized in that: The preparation method comprises: S1: Provides silanophilic monomers, template polymers, and flexible monomers; S2: adding the silophilic monomer, the template polymer and the flexible monomer to the first solvent in proportion under a protective atmosphere, adjusting the pH, and obtaining a mixed solution; S3: adding an initiator to the mixed solution, heating and aging, and adjusting the pH to precipitate the template polymer to obtain a block copolymer solution; S4: extracting the block copolymer in the block copolymer solution to obtain a block copolymer binder.
6. The preparation method according to claim 5, characterized in that: The template polymer can serve as a polymerization template for the silicophilic monomer, and the template polymer includes at least one of polyacrylamide, polymethacrylamide, polyallylamine, polyacrylic acid, and polymethacrylic acid.
7. The preparation method according to claim 5 or 6, characterized in that: The mixed solution satisfies at least one of the following characteristics: The amount of the silaphilic monomer added is 4%-16% of the mass of the first solvent; The amount of the flexible monomer added is 4%-16% of the mass of the first solvent; The molar ratio of the silaphilic monomer to the template polymer is 1:1-1.5; The pH of the mixed solution is 4-9.
8. The preparation method according to claim 5, characterized in that: The initiator satisfies at least one of the following characteristics: The initiator comprises at least one of sulfate, redox initiator system, azobisisobutylamidine hydrochloride, azobisisobutylimidazoline hydrochloride, azobisisobutylimidazoline, and azobiscyanovaleric acid; The added amount of the initiator is 0.5%-1% of the total mass of the silophilic monomer and the flexible monomer.
9. The preparation method according to claim 5, characterized in that: The step S3 satisfies at least one of the following characteristics: The heating temperature is 40-80°C; The heating time is 2-6h; The aging time is 24-48h.
10. The preparation method according to claim 5, characterized in that: A second solvent is added into the block copolymer solution to extract the block copolymer binder, wherein the second solvent comprises at least one of ethanol, propanol, butanol and tetrahydrofuran.